2022
DOI: 10.2340/actadv.v102.4524
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Nails and Long-lasting Nail Polish in Danish Hairdressers: Self-use, Occupational Exposure and Related Eczema

Abstract: Artificial nail modelling systems (ANMS), encompassing artificial nails and long-lasting nail polish, are sources of acrylate exposure in beauticians and users of ANMS. Hairdressers’ exposure to ANMS from self-use and occupational exposure is currently unknown. In 2020 a questionnaire was sent to all hairdressers graduating during 2008 to 2018 in Denmark (n = 4,830). Self-use of ANMS was reported by 87.6% of respondents (1,251/1,428), and application of ANMS to others was reported by 22.1% (316/1,428). Of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…ANMS are mainly applied in nail studios by professionals. In some European countries, ANMS are indicated as a part of the training curriculum of hairdresser apprentices 27 and hairdressers also perform ANMS to their customers in hairdresser salons 28,29 similar to the hairdresser applying ANMS in our series (Table 2). Indeed, in a recent systematic review, the risk of sensitization to 2‐hydroxyethyl methacrylate (HEMA) was found to be increased ninefold in hairdressers and beauticians who were in charge of ANMS compared with controls 27 …”
Section: Discussionmentioning
confidence: 99%
“…ANMS are mainly applied in nail studios by professionals. In some European countries, ANMS are indicated as a part of the training curriculum of hairdresser apprentices 27 and hairdressers also perform ANMS to their customers in hairdresser salons 28,29 similar to the hairdresser applying ANMS in our series (Table 2). Indeed, in a recent systematic review, the risk of sensitization to 2‐hydroxyethyl methacrylate (HEMA) was found to be increased ninefold in hairdressers and beauticians who were in charge of ANMS compared with controls 27 …”
Section: Discussionmentioning
confidence: 99%
“…Los sistemas de modelado de uñas artificiales y esmaltes de larga duración, son fuentes de exposición al acrilato en esteticistas, una elevada exposición se ha relacionado con eccema de manos (Havmose et al, 2022), además es un agente neurotóxico que causa neuropatía periférica con deterioro en brazos y piernas (Park, 2021). Los cosméticos y productos para tinturar el cabello producen irritaciones en la piel, alergias y deterioro de la función pulmonar (Macan et al, 2022).…”
Section: Estilistasunclassified